IMPLEMENTASI UNDANG-UNDANG NOMOR 5 TAHUN 1960 TENTANG PERATURAN DASAR POKOK-POKOK AGRARIA KAITAN DENGAN PERLINDUNGAN HAK ATAS TANAH MASYARAKAT ADAT PUBABU, DESA LINAMNUTU, KECAMATAN AMANUBAN SELATAN, KABUPATEN TIMOR TENGAH SELATAN - Fasri Ferroh; Husni Kusuma Dinata; Chatryen M Dju Bire (Petitum Law Journal, 2026)
This research is an empirical study that aims to determine and analyze the implementation of the basic agrarian law and its obstacles in protecting the land rights of the Pubabu indigenous community, Linamnutu Village, South Amanuban District, TTS Regency. This research was conducted in Linamnutu Village. The types of data used were primary data and secondary data. The data collection techniques used were interviews and literature studies. The population in this study were the Head of East Nusa Tenggara State Land Agency Region, Head of Amanuban Selatan Sub-District, Head of Linamnutu Village, Usif (King) of Amanuban, Pubabu Indigenous Community Leaders. The sample used in this research is a saturated sample technique with a total of 8 respondents. This research shows that, the implementation of the Basic agrarian law in the Pubabu case reveals a systematic failure that requires fundamental reformulation from a technocratic paradigm towards a transformative paradigm. the obstacles to the implementation of the Basic agrarian law in protecting the land rights of Pubabu indigenous peoples, in Linamnutu Village are not solely caused by administrative technical issues, but reflect stronger structural problems in the Indonesian government system.